Dialogue Rhythm in the Dramatic Dialogue "Abu al-Sa'alik" Play : an Example. (Journal of Hama University, 2025)
Tha main idea of the research is about defining the principles on which rhythm is based upon in the dramatic dialogue in "Abu al-Sa'alik" play written by Ghazi Tulaimat. These principles include the internal music represented by some allegorical and phonological features, repetition, intertextuality, reordering and displacement. It also includes the external music represented by the traditional prosodic meters, rhythmic omission, different meters and rhymes in the play. I discussed the first chapter because of the limited space of the reseach on the one hand, and because I wanted to shed light on this sort of dialogue since very few researches are concerned with prosody and rhythm of texts in general, and those concerned with dramatic poetry in particular.